Diet-regulated behavior: FVB/N mice fed a lean diet exhibit increased nocturnal bouts of aggression between littermates - Murph, Mandi M; Liu, Shuying; Jia, Wei; Nguyen, Ha; MacFarlane, Megan A; Smyth, Susan S; Kuppa, Sudeepti S; Dobbin, Kevin K (Laboratory animals (London), 2020)
The hyperactive FVB/N inbred mouse strain is widely used for transgenic research applications, although rarely for behavioral studies. These mice have visual impairments via retinal degeneration, but are considered highly intelligent and rely largely on olfaction. While investigating diet-induced obesity in autotaxin transgenic FVB/N mice, we observed an increase in the necessity for male, but not female, cage separations. Based on the observations, we hypothesized that feeding FVB/N mice a lean diet increases nocturnal bouts of aggression between male littermates. The diets of adult littermates were switched from normal chow to either ad libitum high-fat (45% fat) or lean (10% fat) matched diets for 27 weeks, whereby the mice reached an average of 43 g versus 35 g, respectively. Then, cage separations due to nocturnal bouts of aggression became mandatory, even though littermates peacefully cohabitated for 10–16 weeks previously. Since the data was of an unusual nature, it required uncommon statistical methods to be engendered to evaluate whether and where significance existed. Therefore, utilizing the randomization and population models, we established a methodology and postulated that either testosterone, the autotaxin transgene or diet alteration was the causal factor. Statistical evaluation demonstrated a significant correlation between cage separations and aggressive behavior associated with the lean-diet-fed mice, not autotaxin. Biochemical data did not appear to explain the behavior. In contrast, energy metabolism highlighted differences between the groups of normally hyperactive mice by diet. This characteristic makes FVB/N male mice unsuitable subjects for long-term studies with lean-diet modifications.